Applying International Humanitarian Law in Judicial and Quasi-Judicial Bodies
VII, 508 p.
Keywords: International humanitarian law has been perceived till now as encompassing only judicial cases concerning refugee protection or war crimes prosecutions, particularly in domestic fora. Yet, the last decade has witnessed a revolution in the way judicial bodies—international and domestic alike—are ready to tackle complex security aspects pertaining to the laws of war. The present volume follows the international and domestic courts’ jurisprudential evolution as they deal with issues like the classification of armed conflicts, direct participation in hostilities and the nexus between international humanitarian law and human rights law. Projecting the field’s jurisprudential development, the volume examines the role of international humanitarian law also in the realms of quasi-judicial bodies. Derek Jinks, University of Texas, School of Law, Austin, Texas, USA. Jackson Nyamuya Maogoto University of Manchester, School of Law, Manchester, UK. Solon Solomon King’s College London, Dickson Poon School of Law, London, UK.